A TIME SYNCHRONIZED HYBRID VEHICULAR AD HOC NETWORK OF ROADSIDE SENSORS AND VEHICLES FOR SAFE DRIVING - Sam, Dahlia; Raj, V Cyril (Journal of computer science, 2014)
VANET is a type of ad hoc network in which the moving vehicles act as nodes. There has been lot of research for using VANETs in many applications. One of the main applications is the use of VANETs to improve driving safety. In any safety related applications, the vehicular nodes have to constantly communicate with each other and the roadside equipments. For eg, the roadside units sense real time information about road conditions, road blocks or animals straying on the road and passes the message to the approaching vehicles. The alert message enables the driver to take timely decisions in preventing accidents or delay. However, there are some issues in the above system. One problem is that, VANETs are subject to frequent network disconnections especially in low traffic areas. To overcome the above issues and make the system more reliable, the authors have proposed to include roadside wireless sensor nodes along with the vehicular nodes in the network.